Smart Campus 5G and IoT network preparations for operational mode: Specification to deploy data and network management - Risto Jurva; Marja Matinmikko-Blue; Ville Niemelä; Tuomo Hänninen (International Telecommunications Society (ITS), 2020)
Digitalization activities have been in process for several years covering most business areas. Enterprises around the globe have been preparing their digital transition by the deployment of novel ICT and IoT systems to strengthen their operational functions on many levels. It is envisioned that most businesses will benefit largely from digitalization. This applies also to research and education sector, where the universities are in role to show the way forward. Specifically, the campuses with ICT, cellular network technology and software research units are probably in the frontline to innovate and pilot sophisticated education and research environments. Utilization of data collected from specific surroundings by sensors, devices, machines, vehicles and individuals is increasingly in the focus of developing new services and applications in campuses. The discussion of data based services and applications has been increasing in recent years and emergence of specific data operators has been anticipated. Prior to the development of services and applications, it is important to specify the platforms for data management process for appropriate handling of data. A proper data management process consists of collection, warehousing, processing, refining and sharing of data while not forgetting privacy and security. Stakeholders like universities, business parks or cities are considering to initiate data operator activity by bringing open data available for service and application developers. Subsequently, another aspect with the data operator is the operation of network infrastructure. The campus discussed in this article has deployed 5G and IoT-sensor test network with edge and cloud computing functionality for research purposes. Complementary functionality like network management will be integrated in the next phase of network infrastructure development. In this paper we define the requirements on how to develop digital smart campus environment for data management and network infrastructure operations to establish an operative 5G/IoT network for research purposes. The requirement evaluation is done based on practical campus network use case in progress. Establishment of experimental 5G/IoT operative functions on campus enables to accelerate procreation of research based innovations specifically when the environment is open for enterprises, developers and innovators like the in the campus presented here. The innovations are piloted in the campus surroundings and the most promising ones are up-scaled to develop city governance or to offer services for smart city inhabitants. The most successful innovations will be scaled nationally and globally. Subsequently, a locally operated experimental 5G/IoT network infrastructure on campus advances to find novel approaches in telecom regulation and models for future telecom market which is foreseen to change significantly.
Keywords: 330; 5G; IoT; data management; network management; smart campus